IMPACT STRENGTH OF HORIZONTAL BAMBOO FIBER AND IRON SAND WITH EPOXY MATRIX - Billy Putra Novanda; Haris Ardianto; Hery Setiawan (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2022)
Composite is a material composed of 2 materials, namely matrix and filler. Natural fibers, especially bamboo fibers and iron sand that are waste in Indonesia, have the potential to be developed as engineering materials for composite materials reinforced with natural materials. Therefore, the researcher used bamboo fiber and iron sand as a filler and epoxy resin as a matrix. The method used in this research is experimental. Impact test aims to determine the mechanical properties of the composite to be tested. In the manufacture of composite specimens, researchers used the hand lay-up method in accordance with the ASTM D 6110-10 standard. Meanwhile, to see the physical properties, researchers used macro photos to see the difference in composite fractures after impact testing. This study aims to determine the impact strength of horizontal bamboo fiber composites and iron sand with an epoxy matrix. The composite was made with fraction 1 (50% epoxy matrix and 50% horizontal bamboo fiber), fraction 2 (50% epoxy matrix and 50% iron sand), fraction 3 (50% epoxy matrix, 20% horizontal bamboo fiber and 30% iron sand ). The results of the charpy impact test showed that the impact strength of the composite fraction 1 was 50 KJ/m². for the composite test fraction 2 has an impact strength is 23 KJ/m². Meanwhile, fraction 3 produces an impact strength is 30 KJ/m². It can be seen from the results of the macro photo that the specimens of fractions 1 and 3 have fiber pull-outs, while for fraction 2 it can be seen that the sand grains absorb resin well.